2020
DOI: 10.1021/acs.jpcb.0c00088
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photochemistry of the [Cr(NCS)6]3– Complex in Dimethyl Sulfoxide and Dimethylformamide upon Excitation into Ligand-Field Electronic State

Abstract: The ultrafast photochemistry of the [Cr­(NCS)6]3– complex upon excitation to the 4T2 ligand-field (LF) state was studied in dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) in a wide temporal range (100 fs to 9 ms) by a combination of femtosecond and nanosecond transient absorption spectroscopy techniques and supported by quantum-chemical DFT/TD-DFT calculations. The initially excited 4T2 state undergoes intersystem crossing to the vibrationally hot 2E state with time constants of 1.1 ± 0.2 and 1.8 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To quantify the VR and IC time constants, we analyzed the transient absorption peak integrated over the absorption band. The integrated transient absorption peak area as a function of delay time is expected to consist of the vibrational relaxation and the excited-state population decay components. , We integrated the Δ A spectra over the 660–930 nm absorption band (Figure ), and the resulting function was fitted by the double exponential decay: fast rise (τ 1 ) and the slow decay (τ 2 ); τ 1 = 27 ± 1 fs and τ 2 = 2.58 ± 0.02 ps for ACN and τ 1 = 37 ± 1 fs and τ 2 = 7.3 ± 0.2 ps for DCM. As mentioned above, the fast rise component τ 1 corresponds to the population rise of the LF state formed from the initially excited LMCT state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the VR and IC time constants, we analyzed the transient absorption peak integrated over the absorption band. The integrated transient absorption peak area as a function of delay time is expected to consist of the vibrational relaxation and the excited-state population decay components. , We integrated the Δ A spectra over the 660–930 nm absorption band (Figure ), and the resulting function was fitted by the double exponential decay: fast rise (τ 1 ) and the slow decay (τ 2 ); τ 1 = 27 ± 1 fs and τ 2 = 2.58 ± 0.02 ps for ACN and τ 1 = 37 ± 1 fs and τ 2 = 7.3 ± 0.2 ps for DCM. As mentioned above, the fast rise component τ 1 corresponds to the population rise of the LF state formed from the initially excited LMCT state.…”
Section: Resultsmentioning
confidence: 99%
“…The UV−vis spectra were measured using a Lambda 1050 (Perkin Elmer) UV−vis−NIR spectrophotometer. 34 We used a set of 0.1, 1, and 10 mm quartz cuvettes. All measurements were performed at room temperature, 21 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…4 T 1g (F) transition. [22,23,32,82,83,85,88,89] The UV-visible and FTIR absorbance spectra confirmed the binding of the thiocyanate ligand via its N-terminal to the Cr(III) ion centre.…”
Section: Uv-vis Spectrophotometrymentioning
confidence: 88%
“…19 Studies of the ultrafast to millisecond excited state evolution in [Cr(NCS) 6 ] 3− showed multiple pathways for relaxation and photochemistry. 20 simulations of ultrafast decay rate constants for Ru complexes were presented. It was shown how relaxing the assumption of sequential exponential decay can lead to new mechanistic information.…”
mentioning
confidence: 99%
“…Ultrafast transient absorption (TA) of CuCl 4 2– revealed state dependent photochemistry, with a low lying ligand field energy level being photoinactive, while a higher energy LMCT state was dissociative . Studies of the ultrafast to millisecond excited state evolution in [Cr­(NCS) 6 ] 3– showed multiple pathways for relaxation and photochemistry . Kinetic simulations of ultrafast decay rate constants for Ru complexes were presented.…”
mentioning
confidence: 99%